HUBUNGAN MOBILISASI DINI POST SECTIO CAESAR (SC) DENGAN PROSES PENYEMBUHAN LUKA OPERASI DI RSUD DR.RM.PRATOMO - yadriati maya pesa (Jurnal Ilmu Kebidanan, 2020)
Caesarean section is a surgical procedure wherein the fetus is born through a surgical incision in the wall of the mother's abdomen or uterus that aims to save the life of both the mother and fetus. With early mobilization of uterine contractions will be good so that the hard uterine fundus, the risk of abnormal bleeding can be avoided. This research is a descriptive analytic study with cross sectional design. The subjects of the study were 90 post sc mothers in a hospital that was taken by systematic random sampling. Data collection uses medical records. Statistical tests using the chi square test. Of the 90 post-scanned mothers who mobilized early as many as 48 people (53.3%) while those who did not mobilize as many as 42 people (46.7%) while those who had a rapid wound healing process were 50 people (55.6%) while the healing process the wound was slow as many as 40 people (44.4%). In this study the results obtained that there is a relationship between early sc mobilization post sc with the process of wound healing operations with Chi-Square analysis results obtained P Value 0.001 <(0.05).